Glycaemic effects of a 156-km ultra-trail race in athletes: an observational field study - Parent, C.; Mauvieux, B.; Lespagnol, E.; Hingrand, C.; Vauthier, J.-C.; Noirez, P.; Hurdiel, R.; Martinet, Q.; Delaunay, P.-L.; Besnard, S.; Heyman, J.; Gabel, V.; et al. (Sports Medicine, 2024)
Background: Ultra-trail running races pose appreciable physiological challenges, particularly for glucose metabolism. Previous studies that yielded divergent results only measured glycaemia at isolated times. Objectives: We aimed to explore the impact of an ultra-endurance race on continuously measured glycaemia and to understand potential physiological mechanisms, as well as the consequences for performance and behavioural alertness. Methods: Fifty-five athletes (78% men, 43.7 ± 9.6 years) ran a 156-km ultra-trail race (six 26-km laps, total elevation 6000 m). Participants wore a masked continuous glucose monitoring sensor from the day before the race until 10 days post-race. Blood was taken at rest, during refuelling stops after each lap, and after 24-h recovery. Running intensity (% heart rate reserve), performance (lap times), psychological stress, and behavioural alertness were explored. Linear mixed models and logistic regressions were carried out. Results: No higher risk of hypo- or hyperglycaemia was observed during the exercise phases of the race (i.e. excluding stops for scientific measurements and refuelling) compared with resting values. Laps comprising a greater proportion of time spent at maximal aerobic intensity were nevertheless associated with more time > 180 mg/dL (P = 0.021). A major risk of hyperglycaemia appeared during the 48-h post-race period compared with pre-race (P < 0.05), with 31.9% of the participants spending time with values > 180 mg/dL during recovery versus 5.5% during resting. Changes in circulating insulin, cortisol, and free fatty acids followed profiles comparable with those usually observed during traditional aerobic exercise. However, creatine phosphokinase, and to a lesser extent lactate dehydrogenase, increased exponentially during the race (P < 0.001) and remained high at 24-h post-race (P < 0.001; respectively 43.6 and 1.8 times higher vs. resting). Glycaemic metrics did not influence physical performance or behavioural alertness. Conclusion: Ultra-endurance athletes were exposed to hyperglycaemia during the 48-h post-race period, possibly linked to muscle damage and inflammation. Strategies to mitigate muscle damage or subsequent inflammation before or after ultra-trail races could limit recovery hyperglycaemia and hence its related adverse health consequences.